Structural impact due to PPQEE deletion in multiple cancer associated protein - Integrin αV: An In silico exploration. (December 2020) - Bhattacharya, Shreya; Sah, Pragati Prasad; Banerjee, Arundhati; Ray, Sujay
Abstract: A heterodimeric receptor subunit, Integrin αV, often complexed with Integrin β3 plays a vital role in cell signaling to regulate angiogenesis and promote cancer progression. The paramount β-turn formed from pentapeptide residues (PPQEE) in the cytoplasmic domain of Integrin αV was previously reported as crucial for cell signaling and its deletion was proved deleterious for protein's cell membrane adhesion and ligand binding properties. This study revealed conformational changes in the Integrin αV subunit upon deletion of PPQEE residues through in silico structural modelling approach followed by analysis of alteration of binding sites. Human Protein Atlas database helped to identify the association of Integrin αV to the unfavourable prognosis of three gastrointestinal cancers: stomach, liver and pancreatic cancers. Molecular modelling and docking techniques were carried out for the necessary complex formations (wild-type and mutant-type). Further comparison was performed for the complexes. The changes in protein's conformation and stability due to PPQEE deletion were observed in both independent subunit and heterodimer. The most noteworthy conformational shift was the disruption of a transmembrane helix into coil, which accounted for protein's impaired cell membrane adhesion, increased solvent accessibility and decreased stability. The deletion also caused a reduction of beta-turn regions, which disrupted ligand binding in the cytoplasmic domain of Integrin αV subunit. This study emphasized on structural basis of how the deletion of PPQEE residues alters stability, ligand binding and signaling activity of Integrin αV subunit highlighting the importance of these residues in maintenance of protein's native structure.